Societal Implications of IT in Religion for Developing Countries - Murumba, Julius; Omuya, Erick Odhiambo (My University, 2017)
Information Technology has penetrated nearly all aspects of our daily lives such that relationships associated with individuals and organizations are digitally enabled and mediated. Advances in IT have led to changes in the way religious worship has traditionally been done, ushering in a new age of worship that is augmented by or anchored on a digital platform. The paper aimed at investigating societal implications of IT use in religion and to better understand the ways in which IT affects modernization of religion in developing countries. The objectives of the paper were to establish the types of IT applications being used in religion, the co-existence of IT and religious tradition and how use of IT affects the future of religion. The study was conducted through a desk search. The paper concludes that religion and technology have had some form of inter dependence on one another, and therefore for modernization of religion IT will increasingly play an important role. Religion must adopt ways to utilize IT positively while shunning negative aspects that IT can be used for in religion such as propagation of fundamentalism and extremism through IT
Keywords: Information Technology; Religion; Co-Existence